2012
DOI: 10.1029/2011jd016555
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Earth rotation excitation in data‐constrained and unconstrained atmosphere models

Abstract: [1] Changes in Earth rotation are strongly related to fluctuations in the angular momentum of the atmosphere, and therefore contain integral information about the atmospheric state. Here we investigate the extent to which observed Earth rotation parameters can be used to evaluate and potentially constrain atmospheric models. This is done by comparing the atmospheric excitation function, computed geophysically from reanalysis data and climate model simulations constrained only by boundary forcings, to the excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Chao and Au (1991) showed that during 1980-88, the amplitude of the prograde annual polar motion excitation can be accounted for by atmospheric wind and pressure fluctuations, with equatorial winds contributing about 25% and pressure fluctuations contributing about 75% to the total atmospheric excitation. Discrepancies as large as a factor of two in amplitude were also found by Chao and Au (1991) between observed semiannual polar motion excitation and that due to atmospheric processes (also see Aoyama and Naito, 2000;Barnes et al, 1983;Chao, 1993;Dobslaw et al, 2010;King and Agnew, 1991;Kolaczek et al, 2003;Merriam, 1982;Nastula and Kolaczek, 2002;Nastula et al, , 2009Neef and Matthes, 2012;Stuck et al, 2005;Wahr, 1983;Wilson and Haubrich, 1976;Zhou et al, 2006Zhou et al, , 2008. Furthermore, no agreement was found by Chao and Au (1991) between the observed retrograde annual polar motion excitation and that due to atmospheric processes, with atmospheric excitation being about twice as large as the observed excitation.…”
Section: Seasonal Wobblesmentioning
confidence: 97%
See 3 more Smart Citations
“…Chao and Au (1991) showed that during 1980-88, the amplitude of the prograde annual polar motion excitation can be accounted for by atmospheric wind and pressure fluctuations, with equatorial winds contributing about 25% and pressure fluctuations contributing about 75% to the total atmospheric excitation. Discrepancies as large as a factor of two in amplitude were also found by Chao and Au (1991) between observed semiannual polar motion excitation and that due to atmospheric processes (also see Aoyama and Naito, 2000;Barnes et al, 1983;Chao, 1993;Dobslaw et al, 2010;King and Agnew, 1991;Kolaczek et al, 2003;Merriam, 1982;Nastula and Kolaczek, 2002;Nastula et al, , 2009Neef and Matthes, 2012;Stuck et al, 2005;Wahr, 1983;Wilson and Haubrich, 1976;Zhou et al, 2006Zhou et al, , 2008. Furthermore, no agreement was found by Chao and Au (1991) between the observed retrograde annual polar motion excitation and that due to atmospheric processes, with atmospheric excitation being about twice as large as the observed excitation.…”
Section: Seasonal Wobblesmentioning
confidence: 97%
“…Like seasonal variations in LOD, variations on interannual timescales are also predominantly caused by changes in the angular momentum of the zonal winds (e.g., Eubanks, 1993;Hide and Dickey, 1991;Lambeck and Hopgood, 1981;Neef and Matthes, 2012;Rosen, 1993;Yu et al, 1999). The most prominent feature of the climate system on these timescales is the ENSO phenomenon.…”
Section: Interannual Variations and Ensomentioning
confidence: 99%
See 2 more Smart Citations
“…To explore this in detail, however, tailored data assimilation studies following, e.g., the experimental set-up of Neef and Matthes [2012] need to be performed. Best results are expected during boreal winter, where barotropic conditions dominate and surface wind characteristics are therefore representative for the large-scale atmospheric flow in the lower troposphere.…”
Section: Discussionmentioning
confidence: 99%